The Fifth Plague - Cole, Lucinda. author. aut Link
XII, 260 p. 10 illus., 1 illus. in color.
Keywords: This book examines murrain, or mass mortalities of cattle, in ways that bridge the gap between animal studies and the health humanities. Beginning with early modern European disease ecologies but informed by contemporary epidemiological and ecological concerns, The Fifth Plague offers a new historical approach to literary plague studies, one taking seriously real and imagined relationships between human outbreaks, such as bubonic plague and cholera, and a series of even more mysterious animal diseases that killed in equally great numbers. Chapters include careful readings of literary texts by, among others, William Shakespeare, John Dryden, Daniel Defoe, and Sophie Amelia Prosser. Uniting these readings is a shared history of murrains recorded in Virgil, but also the powerful legacy of the Ten Plagues of Egypt narrative, in which human and non-human afflictions are materially and theologically bound. “Great mortalities” of cattle, Cole argues, brought with them feelings of individual and collective vulnerability. As scientists and humanists face increasingly politicized information networks, this book calls for an exploration of the past, present, and future of humanity’s decidedly interdependent and zoonotic existence. Lucinda Cole is Associate Professor in the Department of English at University of Illinois Urbana-Champaign, USA. She previously published Imperfect Creatures: Vermin, Literature, and the Sciences of Life, 1600-1740 (2016).